Unusual Case of Ovotesticular DSD Presented at Adulthood with Mosaic Karyotype, Full Functioning Mullerian Structure, Two Ovaries, and One Ovotestis - Khalid, Rayan; Siddig, Alaa M.; Elzien, Abdelbagi E. M.; Abudoam, Abdelrahman A.; Fadl-Elmula, Imad (Ethiopian Journal of Reproductive Health, 2024)
Disorder of Sex Development (DSD) is a condition where there is a misalignment of gonads or chromosomes with the genitalia. One of the rarest forms of DSD is Ovotesticular DSD (OT-DSD) which is also known as True Hermaphroditism. It is characterized by the presence of both ovarian and testicular tissues in the same individual. This condition usually presents with ambiguous genitalia either at birth or later in life. OT-DSD is a rare form of DSD, with an estimated incidence of less than one in every 20,000 individuals, which represents less than 5% of all DSD cases. However, it appears to be more common in African countries such as Kenya or South Africa. OT-DSD often displays a diverse range of phenotypes with varying penetrance. In this report, we describe a rare case of OT-DSD where the individual was raised as a female and presented with ambiguous genitalia, a fully functioning Mullerian structure in adulthood, and 3 gonads. We provide clinical and genetic details of the case and review relevant literature on the subject.